Knockdown of miR-21-5P targets and regulates PDCD4-induced apoptosis in ovarian granulosa cells and ameliorates in sulin resistance in polycystic ovary syndrom - Hengzhen He; Peng Ning; Xiaohong Chen; Jing Lin (PLoS ONE, 2026)
This study examined the role of miRNA-21-5p in a rat model of polycystic ovary syndrome with insulin resistance (PCOS-IR) and its potential involvement in ovarian granulosa cell apoptosis. Female Sprague-Dawley rats were divided into four groups, with the PCOS-IR model established using dehydroepiandrosterone combined with a high-sugar, high-fat diet. Lentiviral transduction was utilized to silence miRNA-21-5p. Serum hormone levels were assessed via ELISA, while the protein expression of PDCD4, Bcl-2, and Caspase-3 in ovarian tissues was analyzed through Western blotting. Granulosa cell apoptosis was evaluated using CCK-8 assay, flow cytometry, and TUNEL staining. The targeting relationship between miRNA-21-5p and PDCD4 was confirmed via dual-luciferase reporter assay and further supported by AlphaFold3 and RNA immunoprecipitation (RIP) prediction. Compared to the PCOS-IR and si-NC groups, the si-miRNA-21-5p group displayed improved ovarian morphology, partially restored hormone levels, moderately enhanced insulin sensitivity, and reduced granulosa cell apoptosis, alongside altered PDCD4 expression. These findings suggest that miRNA-21-5p may play a role in the pathogenesis of PCOS-IR by regulating PDCD4 and influencing granulosa cell apoptosis. Inhibition of miRNA-21-5p shows potential in alleviating certain pathological features within this experimental model; however, further validation in human studies is needed to assess its clinical relevance and therapeutic applicability.